Distance Learning as A Strategic Priority of University Education - Monika Zatrochova; Lubomir Spirko (Communications of International Proceedings, 2023)
Distance learning is an active and technological method of education that significantly promotes self-discipline of the individual. That is, a set schedule of course instruction can build self-discipline and commitment. One of the advantages of distance learning is the availability of lessons and information over time. The article discusses the issue of distance learning in university education, which nowadays has to accept new technologies, trends, information and approaches in terms of competitiveness of university graduates and labour market requirements. In the contemporary era, developed countries worldwide use digitization as a progression strategy in education, in general, and in economic education, in particular. (Pasa, A., T., 2020)
Keywords: Distance learning; Labor market; University education; Industry 4.0